A Decade of Iron and Steel in Canada - Alfred W. G. Wilson (Canadian Institute of Mining, Metallurgy and Petroleum, 1938)
THE state of development of its iron and steel industries serves as a 1eading index to the general condition of a nation's business affairs. In this paper, the authors present an economic study of the progress of this group of industries in Canada for the decade 1927-1936. The statistical data and most of the tables which accompany this article have been com-piled by John Casey, Statistician, Bureau of Mines; the text and some of the computations have been prepared by the seni0r author. The principal source of statistical information has been the publications of the Dominion Bureau of Statistics; where other sources have been consulted, they are noted in the text. All weights are given in short tons. Records for the years 1913 and 1918 are also presented in the group of tables dealing with iron ore and pig iron; they will serve as a basis for comparison with nearly normal years in the two decades prior to 1927-36, which included the abnorma1 years of the Great War. GENERAL REVIEW At the beginning of the decade under review, this group of industries had returned to almost normal production, as determined by pre-war conditions. Iron ore consumption showed a steady increase between 1927 and 1930; a marked decline began in 1930 and reached its culmination in 1932, when the recorded consumption of ore was 293,353 to11s, about 16 per cent of the average consumption during the first four years of the decade; the last four years of the decade show a gradual increase in consumption; the amount of ore used in 1936 was still slightly below the amount used ten years before, in 1927 (see Table 1, top).